Using Commercial Letters in Handayani Mart Sekaran in the Disruption Era - Kuswantoro, Agung; Rizqiyah, Riza; Amaliyah, Faidatul; ., Deviani; Damayanti Safitri, Devita (KnE Social Sciences, 2020)
The purpose of this study is (1) to find out the commercial letters used in Handayani Mart to find out which commercial letters are not used in Handayani Mart. In this study is using descriptive qualitative approach. Commercial letters used by Handayani Mart are sales-purchase agreement letters and employment contract agreement For other types of commercial letters such as letters of request for offers, offers, orders, announcements, and certificates made by digital/electronic means. Suggestion in this study are for managers of Handayani Mart should make a central or centralized letter application so that the letter are same in their management, both letters for internal and external requirements. Keywords: District Era, Commercial Letter, Handayani Mart